Advances in Development of PM2.5-Exposed Animal Models and Their Application in Reproductive Toxicity Research - TIAN Fang; PAN Bin; SHI Jiayi; XU Yanyi; LI Weihua (Shiyan dongwu yu bijiao yixue)
Atmospheric fine particulate matter (particulate matter 2.5,PM2.5) is a major component of haze, and its potential hazards to human reproductive health have garnered widespread attention. Establishing appropriate animal models is crucial for in-depth research into the reproductive toxicity of PM2.5 exposure and its underlying mechanisms. This paper, based on recent literature, summarizes current methods for establishing PM2.5-exposed animal models and the evaluation criteria for reproductive toxicity research. The primary modeling methods for PM2.5 exposure include whole-body inhalation exposure and intratracheal instillation exposure. While whole-body inhalation exposure effectively simulates real-life human inhalation environments, it requires sophisticated experimental equipment. Conversely, intratracheal instillation exposure is more cost-effective and easier to operate but faces challenges in accurately mimicking the distribution and deposition of PM2.5 during natural inhalation. Therefore, researchers must carefully weigh these exposure methods to enhance model rigor and achieve the most realistic simulation of human exposure conditions. When summarizing the application evaluation indicators of PM2.5-induced reproductive toxicity, this review finds that the main indicators of male reproductive toxicity include reduced sperm quality, testicular tissue damage, and hormonal imbalances. For female reproductive toxicity, the primary indicators are reduced ovarian reserve, endocrine dysfunction, endometrial damage, and adverse perinatal reactions. Additionally, this review highlights the need for detailed chemical composition analysis of PM2.5, exploring the reproductive toxic targets and mechanisms of particles containing different chemical components, such as heavy metals and polycyclic aromatic hydrocarbons. Long-term studies are also necessary to assess the effects of PM2.5 exposure on reproductive health and transgenerational effects, to predict potential long-term risks for humans. Additionally, interdisciplinary collaboration should be encouraged, involving cooperation between environmental science, toxicology, reproductive medicine, and other disciplines, to comprehensively assess the environmental health risks of PM2.5 and provide scientific support for the development of integrated prevention and control strategies. This review summarizes animal modeling methods, evaluation criteria, and their applications, providing valuable methodological references for future reproductive toxicity research on PM2.5.